"Brittleworms": Ultrastructure and arrangement of the calcified chaetae of Euphrosine (Amphinomida, Annelida). Issue 4 (19th November 2021) - Müller, Julian; Schumacher, Anja; Borda, Elizabeth; Rouse, Greg W.; Bartolomaeus, Thomas; Tilic, Ekin
Abstract: The annelid clade Amphinomidae, commonly known as "fireworms, " is notorious for causing skin inflammations after physical contact. These injuries are caused by the chaetae of the animals, which are calcified and particularly brittle. The incorporation of calcium carbonate particles and their disintegration cause the chitinous lamellae within a chaeta to break apart and result in a prominent inner cavity. Although the chaetae of Amphinomidae are well studied, data concerning their sister group, Euphrosinidae, are scarce. In this study, we examined the chaetae of two species of Euphrosine for the first time regarding the variety of chaetal types, their ultrastructure, elemental composition, and arrangement. This allows us to get a better understanding of chaetal characteristics in the ground pattern of Amphinomida. We were able to determine bifurcate chaetae as the primary chaetal type in Amphinomida and provide evidence that their aciculae must have evolved secondarily. Calcification is a common feature among amphinomidan chaetae and regarded as autapomorphy of Amphinomida. Finally, a single dorsal formative site in each notopodium and neuropodium, found in Euphrosine foliosa, likely represents the ancestral state in Amphinomida. There is no evidence for venom production or secretory cells associated with the chaetae of Euphrosine, which is in accordance with what was previously observed in Amphinomidae. Our study also complements further studies into chaetal characteristics such as the number and arrangement of formative sites.